Modulators of change-of-direction economy after repeated sprints in elite soccer players - Dolci, F.; Kilding, A. E.; Spiteri, T.; Chivers, P.; Piggott, B.; Maiorana, A.; Hart, N. H. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To investigate the acute effect of repeated-sprint activity (RSA) on change-of-direction economy (assessed using shuttle running economy [SRE]) in soccer players and explore neuromuscular and cardiorespiratory characteristics that may modulate this effect.